Potential Use of Expired Starch for Practicum Materials as an Effort to Reduce Chemical Laboratory Waste - Rachmawati; Wati, Idah Diana; Sa’adah, Ani (Proceeding of International Joint Conference on UNESA, 2024)
The laboratory is a facilitator of scientific activities. The use of chemicals is commonplace but is a factor in increasing waste, mainly unused and expired chemicals. This research aims to determine the potential for reusing starch as a practical material to reduce laboratory waste. The research method used was experimental by comparing expired starch with pro-analysis starch (new condition) and technical starch, including ash content, starch content and infrared spectrum (IR), which were then analyzed using one-way ANOVA. The results showed that the ash content and starch content of expired starch with pro-analysis starch did not have a significant difference (p-value > 0.05) but had a significant difference with technical starch (p-value < 0.05). The IR spectrum of the third starch also does not provide much difference from the correlation value close to 1. So, it can be seen that expired starch still has the potential to be reused as a practical material to reduce laboratory waste. Further research can be conducted to determine further characteristics so that chemicals can be reused at a higher level.